Clostridioides difficile-associated diarrhea in surgical service patients in Mexico - Morfín Otero, Rayo; Petersen Morfin, Santiago; Aguirre Diaz, Sara Alejandra; Pérez Gómez, Héctor Raúl; Garza González, E.; Gonzalez Diaz, Esteban E.; Esparza Ahumada, Sergio; Velarde Ruiz Velasco, José Antonio; León Garnica, Gerardo; Escobedo Sanchez, Rodrigo; Rodríguez Noriega, Eduardo (2020)
Introduction: Clostridium difficile is the first cause of healthcare-associated diarrhea in developed countries. In recent years the incidence of C. difficile infection (CDI) has increased worldwide. There is not much information on the topic in Mexico, and little is known about the risk factors for the infection in patients that are hospitalized in surgical services. Materials and methods: A case-control study was conducted that compared the epidemiologic findings and risk factors between surgical patients with PCR-confirmed CDI, surgical patients with diarrhea and a negative PCR test, and surgical patients with no diarrhea. The statistical analysis was carried out using the SPSS version 22.0 program. Results: The majority of the surgical patients with CDI belonged to the areas of neurosurgery, cardiac surgery, orthopedics, and general surgery. A total of 53% of the CDI cases were associated with the hypervirulent CD NAP1/027 strain. The presence of mucus in stools (OR: 1.5, p = 0.001), fever (OR: 1.4, p = 0.011), leukocytes in stools (OR: 3.2, p < 0.001), hospitalization within the past twelve weeks (OR: 2.0, p < 0.001), antibiotic use (OR: 1.3, p = 0.023), and ceftriaxone use (OR: 1.4, p = 0.01) were independent risk factors for the development of CDI.